Republic of Liberia Economic Update, June 2021 : Finding Fiscal Space - World Bank (World Bank, Washington, DC, 2021)
In the years leading to the Coronavirus (COVID-19) outbreak, Liberia’s economic performance was already weak. Since 2014 a series of severe shocks stopped in its track the growth momentum that had been spurred by the Accra Comprehensive Peace Agreement of 2003. The economy was buffeted by the devastating Ebola outbreak, a collapse in iron ore and rubber prices, and the drawdown of United Nations peacekeeping forces. Monetary and exchange rate policy remained tight in 2020, with the Central Bank of Liberia (CBL) exercising caution in view of uncertainties about the economic impact from Coronavirus (COVID-19). The cash shortages have made headlines and prompted the CBL to provide explanations. Fiscal space can be increased by improving the efficiency of current expenditure. The government needs first and foremost to reduce the very high level of current spending and strengthen domestic revenue mobilization to generate savings for public investments financing. Liberia should remain prudent on external borrowing in its quest to meet the large investment required by the Pro-poor Agenda for Prosperity and Development (PAPD). Finally, Liberia should improve the efficiency of its public investment through better planning, project preparation and management, and better alignment with PAPD priorities.